Varieties of Top Incomes - Sandy Brian Hager (Socio-Economic Review, 2020)
Focusing on the advanced political economies, this article critically reviews the recent scholarship on the evolution of top incomes over the past few decades. The existing literature shows that the determination of top incomes is complex, multifaceted and bound up with factors associated with both politics and economics. Technological change and globalization are vital sources of change in contemporary capitalism, but the continued diversity in top income shares across the advanced capitalist world suggests that these forces alone cannot account for the empirical patterns. Instead, there is compelling evidence that power and politics, including government policy, trade union and left party strength, institutions and financialization, all play a pivotal role in regulating distributive outcomes. It is argued that future research will require a plurality of methodological approaches in order to clarify the complex causal process that drives top-end income concentration.
Keywords: P16; O15; 330; income distribution